2011
DOI: 10.1159/000329293
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Selective Serotonin Reuptake Inhibitor Exposure: Impact on Brain Development and Neural Plasticity

Abstract: Selective serotonin reuptake inhibitor (SSRI) medications are the most common antidepressant treatment used during pregnancy and the postpartum period. Up to 10% of pregnant women are prescribed SSRIs. Serotonin plays an integral part in neurodevelopment, and questions have been raised about the placental transfer of SSRIs and the effects of preventing reuptake of presynaptic serotonin on fetal neurodevelopment. Preclinical data is beginning to document a role of early exposure to SSRIs in long-term developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 107 publications
3
17
0
Order By: Relevance
“…This indicates that PRS was effective in inducing the hyper-responsiveness of the HPA axis, as shown by previous studies, which have demonstrated that early life experiences, including maternal stress, are linked to anxiety and depressed behavior in adolescence and adulthood, in parallel with hyperactivity of the HPA axis [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This indicates that PRS was effective in inducing the hyper-responsiveness of the HPA axis, as shown by previous studies, which have demonstrated that early life experiences, including maternal stress, are linked to anxiety and depressed behavior in adolescence and adulthood, in parallel with hyperactivity of the HPA axis [9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 77%
“…Several clinical and preclinical studies have shown that exposure to maternal mood disorders, maternal stress and other forms of maternal hardship can affect the developing hypothalamic-pituitary-adrenal (HPA) axis [4][5][6][7][8]. Many studies have demonstrated that early life experiences, including maternal stress, are linked to anxiety and depressed behavior in adolescence and adulthood, in parallel with hyperactivity of the HPA axis [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover epigenetic modifications may contribute to developmental outcomes (Kinnally et al, 2010). Overall, early exposure to SSRIs has an effect on brain development and neuroplasticity (for review see: Pawluski, 2012) which can markedly alter the behavior of the offspring.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…It should be emphasized that we examined healthy animals that were not subjected to conditions simulating maternal depression or stress. Maternal stress, which has been shown to influence the actions of developmental SSRI exposure using murine models [46], was therefore not accounted for in the present study design.…”
Section: Discussionmentioning
confidence: 99%